Comparative study between throat swab and ear discharge swabs culture and sensitivity findings in pediatric patients with bilateral chronic otitis media - M. S., Sudhakar Rao; T. P., Navneeth (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic otitis media is one of the common infections seen in pediatric age group. The most widely recognized route of infection is via the eustachian tube. The inflammation of the pharyngeal end of the eustachian tube may prevent gas exchange, leading to lowering of the middle ear pressure and predisposes to aspiration of nasopharyngeal microbes into the middle ear cleft. Methods: Eighty (80) cases of clinically diagnosed chronic otitis media among pediatric age group of both sexes selected on simple random basis were included in this study. Swabs from both ears and throat were taken and the samples were sent under strict aseptic conditions for culture and sensitivity testing. Results: The mean age of patients was 6.1years and the frequency of chronic otitis media was maximum in 1-5 years age group. Male to female ratio was 1.6:1.The most frequent organism isolated was S. Aureus followed by Psuedomonas. The ear swab and throat swab findings showed positive relationship (p<0.05) for the common organisms i.e., S. Aureus, pseudomonas and Streptococcus pyogenes respectively, thus suggesting a common etiological agent. Psuedomonal infection was found to be associated with large perforation in tympanic membrane. Conclusions: The pathology in bilateral ear disease is central i.e., throat. Treatment in these cases is focused on selected drug with optimum dose and calculated regimen of treatment completely, thus reducing the morbidity of loss of physiological function of the ear and the grave complications involved.